Hubungan Berat Badan Kering Pada Pasien Hemodialisis Terhadap Kualitas Tidur dan Kualitas Hidup di Instalasi Dialisis Rumah Sakit Islam Purwokerto - Firdaus Nu’man Septian; Mustiah Yulistiani; Agus Santosa; Tina Muzaenah (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Hemodialysis is the most commonly used renal replacement therapy for end-stage chronic kidney disease (CKD) patients. The hemodialysis process involves regulating the patients dry weight (DW), which is defined as the lowest tolerated weight after a dialysis session without causing symptoms of hypotension or muscle cramps. Sleep quality and quality of life are crucial aspects of care for hemodialysis patients. To analyze the correlation between dry weight and sleep quality as well as quality of life in hemodialysis patients. This study employed a quantitative research instruments included a digital weighing scale, the Pittsburgh Sleep Quality Index (PSQI) questionnaire, and the Kidney Disease Quality of Life Short Form 36 (KDQOL SF-36) questionnaire. The data were analyzed using the Chi-Square test. The Chi-Square test results indicated that the correlation between dry weight and quality of life had a significance value of 1.000 (p 0.05), while the correlation between dry weight and quality of life had a significance value of 0.700 (p 0.05) indicating that neither showed a significant association. There is no significant correlation between dry weight in hemodialysis patients and sleep quality of life at the Dialysis Unit of Purwokerto Islamic. Keywords: Dry weight, sleep quality, quality of life, chronic kidney disease, hemodialysis